The Gothic and the Rule of the Law, 1764-1820 - Chaplin, Sue. author. aut Link
VIII, 183 p.
Keywords: This book is the first full-length theoretical and historical study of the relation between early Gothic fiction and an emerging modern rule of law. The work identifies not only a political and cultural, but also an ontological relation between what critics have conceptualized as 'Gothic' and the nature and function of modern juridical power.